Marcelo Caetano e a Origem do Exercício ALCORA - Luís Barroso (Cadernos de Estudos Africanos)
This paper aims to find the reasons why South African senior military officials were eager to reach an agreement with Portugal to set up a plan for the defence of Southern Africa in 1970, which culminated in the ALCORA alliance. Notwithstanding regional and global settings, stemmed from Cold War, and other political factors, it is possible to argue that the Exercise ALCORA resulted from South Africa’s mistrust of the Portuguese ability to defeat insurgents in Angola and Mozambique. The argument considers the year from 1968 to 1969 as pivotal between the informal collaboration relationship and the perceived requirement to establish a formal one. We conclude that due to Angola’s and Mozambique’s strategic value, we may admit that South Africa wanted to have control over her future in leading a military arrangement that would evolve into the economic, social and political dimensions. Since Exercise ALCORA’s focus was counterinsurgency, a military agreement as its first step was logical, notwithstanding the problem of racial policies.